Book Review Digital Fever: Taming the Big Business of Disinformation, by Bernhard Poerksen - Florența Toader (Romanian Journal of Communications and Public Relations)
The book titled Digital Fever: Taming the Big Business of Disinformation, written by Bernard Poerksen offers a critical analysis of the many crises public discourse faces in the digital age. In addressing the shifting media landscape heavily influenced by the advent of social media, the book reflects on trends like digital disinformation, emotional manipulation, or the erosion of traditional media gatekeepers. Poerksen is a media theorist, who teaches Media studies at the University of Tu¨bingen, and whose works on the new media age have largely been appreciated in Germany.